2023
DOI: 10.1111/nph.18773
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics gives new insights into the ectomycorrhizal degradation of chitin

Abstract: Summary Ectomycorrhizal (EcM) fungi play a crucial role in the mineral nitrogen (N) nutrition of their host trees. While it has been proposed that several EcM species also mobilize organic N, studies reporting the EcM ability to degrade N‐containing polymers, such as chitin, remain scarce. Here, we assessed the capacity of a representative collection of 16 EcM species to acquire 15N from 15N‐chitin. In addition, we combined genomics and transcriptomics to identify pathways involved in exogenous chitin degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 99 publications
1
9
0
Order By: Relevance
“…In particular, we highlight the high expression of AA5 (oxidases), GH5_9 (β‐1,3‐glucanases), GH18 (chitinases), GH20 (β‐N‐acetylglucosaminidases), and GH128 (β‐1,3‐glucanases) families within the ectomycorrhizal guild. Moreover, recent studies have confirmed that certain ectomycorrhizal fungal species use GH18 and GH20 to depolymerize chitin by hydrolytic mechanisms and that degradation of FCW, and in particular chitin, by ectomycorrhizal fungi might be a key functional trait of N cycling in forest soil (Lindahl & Taylor, 2004; Maillard et al ., 2023). However, some traits (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we highlight the high expression of AA5 (oxidases), GH5_9 (β‐1,3‐glucanases), GH18 (chitinases), GH20 (β‐N‐acetylglucosaminidases), and GH128 (β‐1,3‐glucanases) families within the ectomycorrhizal guild. Moreover, recent studies have confirmed that certain ectomycorrhizal fungal species use GH18 and GH20 to depolymerize chitin by hydrolytic mechanisms and that degradation of FCW, and in particular chitin, by ectomycorrhizal fungi might be a key functional trait of N cycling in forest soil (Lindahl & Taylor, 2004; Maillard et al ., 2023). However, some traits (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a significant fraction of plant C is converted into microbial biomass or other microbial products. During fungal decomposition, necromass is recycled by active soil microorganisms, including other fungi (Maillard et al ., 2023). A better understanding of the processes carried out by different fungal groups can be obtained using metagenomics and metatranscriptomics, which enable the description of in situ functional complementarities and competition between functional guilds.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Suillus can act as hosts themselves for a diversity of fungi and bacteria, including related fungi in the genera Gomphidius and Chroogomphus (Olsson et al, 2000;Fig. 1o,p) and bacteria that both associate with living hyphae and mycorrhizas (Izumi et al, 2006;Timonen & Hurek, 2011), and actively decompose dead mycelia (Maillard et al, 2022(Maillard et al, , 2023. Together, these traits offer exciting opportunities to help solve a broad range of ecological and evolutionary questions.…”
Section: Suillus Is An Excellent Model For Ecm Ecology and Evolutionmentioning
confidence: 99%
“…Protein decomposition appears to be dependent on forest age, with Suillus species in younger forests having lower protein decomposition activity (Rineau et al ., 2016), which could be advantageous given that more mature forests contain higher levels of organic nitrogen. Genomic and functional assays have demonstrated that S. luteus also uses endochitinases to decompose complex chitin polymers (Maillard et al ., 2023). Initial work suggests that in low‐carbon soils, S. salmonicolor ( cothurnatus ), like some other ECM species, can prime decomposition by saprotrophic fungi (Bhatnagar et al ., 2021).…”
Section: Ecological Interactionsmentioning
confidence: 99%
“…As ancestral ECM lineages shifted toward symbiotic relationships, the need for these degradative enzymes diminished, resulting in their gradual loss over evolutionary time (Martin & Selosse, 2008; Wolfe et al ., 2012; Lebreton et al ., 2021). This makes mycorrhizal fungi dependent on their host plants for C. Nevertheless, many of the sequenced fungi have maintained a unique array of PCWDEs, including endoglucanases and oxidoreductases/laccases, suggesting that several ECM fungi possess diverse abilities to scavenge plant and microbial detritus (necromass) from soil and litter (Bödeker et al ., 2014; Veneault‐Fourrey et al ., 2014; Op De Beeck et al ., 2018; Pellitier & Zak, 2018; Nicolás et al ., 2019; Floudas et al ., 2020; Maillard et al ., 2023). Fine‐tuned regulation of these PCWDE genes is necessary to avoid triggering plant defense responses (Miyauchi et al ., 2020).…”
Section: Harnessing Genomics To Enhance Our Understanding Of the Deve...mentioning
confidence: 99%